2017
DOI: 10.1159/000475767
|View full text |Cite
|
Sign up to set email alerts
|

Pre-End-Stage Renal Disease Care and Early Survival among Incident Dialysis Patients in the US Military Health System

Abstract: Background: Previous reports showed an increased early mortality after chronic dialysis initiation among the end-stage renal disease (ESRD) population. We hypothesized that ESRD patients in the Military Health System (MHS) would have greater access to pre-ESRD care and hence better survival rates during this early high-risk period. Methods: In this retrospective cohort study, using the US Renal Data System database, we identified 1,256,640 patients initiated on chronic dialysis from January 2, 2004 through Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The 32 studies included in this review represent a combined population of 1 083 264 new dialysis starters and 283 277 person‐years of observation for early mortality. The characteristics of these studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The 32 studies included in this review represent a combined population of 1 083 264 new dialysis starters and 283 277 person‐years of observation for early mortality. The characteristics of these studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, the presence of a maturing AVF/G was more frequent in patients with early access to nephrology care, which is an aspect of pre-ESRD nephrology care that has been underappreciated, although this association has already been shown for presence of mature AVF. [10][11][12] A maturing AVF/G represents a 'near-miss', and future work should involve developing strategies to promote timely AVF/G placement that enables patients to avoid CVC Figure 1. Comparison of the time to transition from a dialysis catheter to a working arteriovenous fistula or graft, between patients with a maturing AVF or AVG at HD initiation and those with a catheter as the sole vascular access.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-dialysis education programmes are now in widespread use across the renal community [1,2]. Informing patients through a shared decision-making process can influence patient treatment decisions and improve outcomes [3,4]. Shared decision making must be underpinned by robust outcome data presented in a way that is meaningful to patients and carers [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%